Acute Effects of Contract–Relax PNF With and Without Neuromuscular Electrical Stimulation on Hamstring Flexibility and Jump Performance in Adolescent Soccer Players: A Randomized Controlled Trial - Carlos Salvador-Huerta; Pedro Azanon-Nogueira; Eloi Suárez-Pazos; Valeria Betancourt-Cabeza; Irene Lazcano-Nogueira; Andrea Porcu; Ángel Manuel de la Hera-Sastre; Juan J. Amer-Cuenca; Juan Francisco Lisón (International Journal of Sports Physical Therapy, 2026)
Background The additional value of neuromuscular electrical stimulation (NMES) during contract–relax proprioceptive neuromuscular facilitation (PNF-CR) stretching remains unclear, particularly in adolescent athletes. It is also unknown whether combining PNF-CR with motor-threshold NMES improves hamstring flexibility more than a sensory-threshold comparator without impairing vertical jump performance. Purpose To compare the acute effects of PNF-CR combined with motor-threshold NMES versus sensory-threshold NMES on hamstring flexibility and to assess the impact of both interventions on vertical jump performance. Study Design Randomized controlled trial. Methods Forty-seven youth soccer players (mean age: 13.2 ± 1.8 years) were randomly assigned to one of two groups. Both groups received the same single-session PNF-CR stretching protocol. The experimental group (n = 23) received motor-level NMES during the contraction phases, whereas the placebo group (n = 24) received sensory-level NMES during the same PNF-CR protocol. Hamstring flexibility was assessed using the Popliteal Angle (PA) and Sit-and-Reach (SR) tests, while vertical jump performance was evaluated via the Countermovement Jump (CMJ) test. Analyses followed an intention-to-treat approach. Time, group, and time × group effects were examined using two-way repeated-measures ANOVA with Bonferroni-adjusted post hoc comparisons; CMJ was additionally analyzed using ANCOVA adjusted for baseline values. Results Both groups showed statistically significant pre–post improvements in SR and PA scores. Specifically, PA decreased in the experimental group by 4.0° (95% CI: 1.4 to 6.5; p = 0.003) and by 3.1° (95% CI: 0.5 to 6.0; p = 0.018) in the placebo group. SR increased by 2.7 cm (95% CI: 1.9 to 3.6; p < 0.001) in the experimental group and 2.8 cm (95% CI: 1.9 to 3.7; p < 0.001) in the placebo group. No significant between-group differences were found for either flexibility outcome. Regarding CMJ, no significant intra- or intergroup changes were observed (p > 0.05). Conclusion The addition of motor-threshold NMES to a PNF-CR stretching protocol does not yield superior acute flexibility gains. Moreover, neither intervention negatively affected jump performance in this athletic population, supporting their safe and potentially beneficial application in pre-training contexts for adolescent soccer players. Level of Evidence 1b.